THE IMPACT OF STRATEGIC INNOVATION ON HOTEL PERFORMANCE IN NANCHANG, JIANGXI, CHINA - Zhou Zhuofan; Wan Aishah Wan Mohd Nowalid (International Journal of Accounting, Finance and Business, 2024)
The hotel industry in Jiangxi area is facing unprecedented levels of competition and new challenges as a result of this growth. Businesses, in order to survive and prosper in this ever-changing environment, need to prioritise strategic innovation. Within the context of Jiangxi's hospitality sector, this research explores the many facets of strategic innovation by zeroing in on three crucial aspects: Innovation development, innovation culture, and innovation competence, and the significant impact they have on organisational performance. The process of systematically developing new ideas, methods, and products is known as innovation development. It stresses the value of systematically identifying opportunities and developing new strategies to achieve goals. The need of encouraging a spirit of innovation among hotel staff is also discussed. By adhering to a set of shared values that promotes inquiry, experimentation, and moderate risk-taking, a company fosters an environment conducive to innovation. A culture like that encourages teamwork, questions the current quo, and adapts to new circumstances with ease. The study emphasises the significance of tailoring innovation techniques to the specific regional environment of Jiangxi, which includes local rules, market dynamics, and cultural norms. Hotel owners and managers that take the time to familiarise themselves with the specifics of their respective regions stand a far better chance of achieving their goals.